Injury-Driven Structural and Molecular Modifications in Nociceptors - Mario García-Domínguez (Biology)
Peripheral tissue injury initiates a multifaceted cascade of structural and molecular modifications within nociceptors, the primary sensory neurons tasked with detecting noxious stimuli. These alterations play a crucial role in the induction and maintenance of pain states, encompassing acute and chronic pain. Structural remodeling includes alterations in axonal architecture, dendritic morphology, and synaptic connectivity, collectively impacting nociceptor excitability and functional integration. Simultaneously, molecular adaptations comprise the regulation of ion channels, receptor expression, and intracellular signaling pathways, as well as transcriptional reprogramming that modulates nociceptive signaling. This review synthesizes current evidence regarding the cellular and molecular bases of injury-induced plasticity in nociceptors, identifying prospective targets for therapeutic intervention to counteract maladaptive sensitization. Elucidating these processes is critical for the advancement of pain treatment strategies and for enhancing clinical outcomes in individuals experiencing neuropathic pain secondary to tissue injury.